2015
DOI: 10.1055/s-0034-1392262
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment of fistula after sleeve gastrectomy: results of a multicenter retrospective study

Abstract: Endoscopic treatment facilitated healing of post-LSG fistula in 74 % of patients. Early endoscopic treatment increased the likelihood of success, and was most effective during the first 6 months of management. After this point, surgical treatment should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 17 publications
1
35
0
Order By: Relevance
“…Most gastric leaks after sleeve gastrectomy require stenting to achieve healing, although alternative treatments have been described. No consensus has been reached concerning the type of stent to be used for gastric leak; many types are available, such as a CS, DPS or over‐the‐scope clip. Few series have compared different types of stent in the endoscopic treatment of gastric leak after sleeve gastrectomy, and no cost analyses of the various types of endoscopic management have been published.…”
Section: Discussionmentioning
confidence: 99%
“…Most gastric leaks after sleeve gastrectomy require stenting to achieve healing, although alternative treatments have been described. No consensus has been reached concerning the type of stent to be used for gastric leak; many types are available, such as a CS, DPS or over‐the‐scope clip. Few series have compared different types of stent in the endoscopic treatment of gastric leak after sleeve gastrectomy, and no cost analyses of the various types of endoscopic management have been published.…”
Section: Discussionmentioning
confidence: 99%
“…There are fewer studies on those sealants than on fibrin glue, usually combining multiple techniques. Thus, we were unable to extract the specific effectiveness of tissue sealant instead of the effectiveness of other methods or combined endoscopic therapy from these studies [82]. Kotzampassi et al demonstrated high efficacy of 96.8% of cyanoacrylate in a heterogeneous series of 8 patients with fistulas after various types of surgery [95].…”
Section: Discussionmentioning
confidence: 97%
“…In addition, we presented the data regarding OTSC therapy from the study describing the use of endoscopic closing techniques alone versus endoscopic drainage (with or without other endoscopic techniques) [72]. We excluded from our analysis studies or study results reporting the concomitant use of stent or stent placement before clipping (Supplementary material, Figure S9) [40,66,70,72,75,77,78,[81][82][83][84][85][86][87][88][89][90][91]. Different definitions of therapy success were applied in the reviewed studies.…”
Section: Clipping Techniquesmentioning
confidence: 99%
“…As a result, there is an important heterogeneity in the management of these patients through the literature and the individual evaluation of each endoscopic modality is very difficult. Accordingly, one recent study has evaluated the overall efficacy of interventional endoscopy in this setting involving different techniques[137]. Among 110 included patients with post-LSG leaks, 74% healed with endoscopic treatment.…”
Section: Anastomotic Leaks and Fistulasmentioning
confidence: 99%